OCTOBER 11, 2016: INTERNATIONAL DAY OF THE GIRL SAVE GIRL CHILD & EDUCATE HER - Patel, Amrit (International Journal of Research -GRANTHAALAYAH, 2016)
Woman is the procreator and the mother of tomorrow shaping the destiny of civilization. For a woman, pregnancy is the most delighted event but in India in some cases the birth of a girl child is a gloomy and despair event and perhaps the gravest concern facing humanity. The United Nations has been observing each year on 8th March “International Women’s Day since 1975 to achieve specified mandate enshrined in its resolution. Subsequently, in order to focus undivided attention to girl child the United Nations, since 2012, has been observing 11th October each year as “International Day of Girl Child”. Acknowledging the significance of the girl child India went ahead and has been observing 24th January each year since 2008 “National Girl Child Day” & National Nutrition Week from September 1-7 since 1982 . It is against this background, this development perspective article briefly highlights the pathetic scenario of girl child worldwide & in India specifically despite the implementation of specific policy & programs in India and suggests strategy to achieve the goal “ Save the girl child & Educate the girl” as a part of United Nations Sustainable Development Goal-4 [“Achieve gender equality and empower all women and girls “by 2030] when India could not achieve UN Millennium Development Goals by 2015 in this regard.